Where are the majors? (Past, Present, and Future of Statistical Science, 2014)
Figure 14.1 suggests that the field of statistics in the US is spectacularly and uniquely unsuccessful in producing Bachelor’s degree graduates when compared with every other undergraduate major for which cognate Advanced Placement (AP) courses exist. In those same subject areas, statistics also produces by far the fewest Bachelor’s degrees when the normalization is taken as the number of doctoral degrees in that field. We are in an era in which demand for statistical/data scientists and analytics professionals is exploding. The puzzle is to decide whether this plot is spur to action or merely an irrelevant curiosity.